1991
DOI: 10.1007/bf02245655
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of antidepressant action by dopamine antagonists in an animal model of depression

Abstract: Rats subjected chronically (12 weeks) to a variety of mild, unpredictable stressors showed a reduced consumption of sucrose or a sucrose/saccharin mixture in two-bottle consumption tests (sweet solution versus water). The deficit was apparent within 2 weeks of stress; normal behaviour was restored by chronic (7 weeks) treatment with the tricyclic antidepressants desmethylimipramine (DMI) or amitriptyline (AMI). Acute administration of the dopamine D1 receptor antagonist SCH-23390 1 week after withdrawal, or th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0
2

Year Published

1993
1993
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(50 citation statements)
references
References 33 publications
3
45
0
2
Order By: Relevance
“…Dopamine has been implicated in neuronal bases of action of antidepressant drugs including SSRIs (D'Aquila et al, 1994(D'Aquila et al, , 2000Gambarana et al, 1995;Sampson et al, 1991). Consistent with our finding, chronic fluoxetine has been shown to increase mRNA levels of the D 1 receptor in the hippocampus (Miller et al, 2008).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Dopamine has been implicated in neuronal bases of action of antidepressant drugs including SSRIs (D'Aquila et al, 1994(D'Aquila et al, , 2000Gambarana et al, 1995;Sampson et al, 1991). Consistent with our finding, chronic fluoxetine has been shown to increase mRNA levels of the D 1 receptor in the hippocampus (Miller et al, 2008).…”
Section: Discussionsupporting
confidence: 90%
“…The dopamine-induced synaptic potentiation at the mossy fiber synapse is mediated by D 1 -like receptors (Kobayashi and Suzuki, 2007). D 1 -like receptors are involved in behavioral effects of antidepressants in animal models of depression (D'Aquila et al, 1994;Gambarana et al, 1995;Sampson et al, 1991). Given the potential involvement of the mossy fiber synapse in mechanisms of action of antidepressants, the dopaminergic modulation at the mossy fiber synapse may also be affected by antidepressant treatments.…”
Section: Introductionmentioning
confidence: 99%
“…As stated above, compounds acting as agonists on dopamine D 2 /D 3 receptors, such as bromocriptine, piribedil, pramipexole, and roxindole (Post et al, 1978;Bouras and Bridges, 1982;Willner, 1983a;Borsini et al, 1988;Muscat et al, 1992;Grunder et al, 1993;Willner et al, 1994;Maj et al, 1996b;Corrigan et al, 2000), and compounds that enhance dopamine levels inhibiting selective dopamine reuptake like amineptine, nomifensine, and bupropion (Kinney, 1985;Dalery et al, 1997), have shown antidepressant-like activity in both preclinical models and clinical settings. Interestingly, it has been proposed that an increase in dopamine activity induced by chronic antidepressant treatments is one of the mechanisms of action underlying the efficacy of these compounds, since their effects are antagonized by low doses of D 2 /D 3 antagonists (Borsini et al, 1984;Borsini et al, 1985a, b;Pulvirenti and Samanin, 1986;Sampson et al, 1991;Serra et al, 1992;D'Aquila et al, 2000a). Moreover, antidepressant treatments are associated with increased dopaminergic function in the mesolimbic system and increased behavioral response to dopamine agonists (Spyraki and Fibiger, 1981;Maj et al, 1984a, b;Cervo and Samanin, 1987;De Montis et al, 1990;Ainsworth et al, 1998a;D'Aquila et al, 2000bD'Aquila et al, , 2003, which takes place after chronic treatment (2-3 weeks), a period of time that correlates with that necessary for the onset of antidepressant activity in the clinic.…”
Section: Discussionmentioning
confidence: 99%
“…Sucrose and saccharin preference, measured to account for possible between-group differences in water consumption, was determined by dividing sucrose or saccharin consumption by total fluid consumption. Consistent with previous studies of the effect of stress on the consumption of highly palatable solutions, all mice were deprived of food and water for 20 hrs preceding each fluid preference test (Papp et al, 1993;Sampson et al, 1991;Willner et al, 1987). Immediately after completion of the fluid preference test, mice had ad lib access to food and water for 4 hrs in their home cages.…”
Section: Fluid Consumptionmentioning
confidence: 91%